SAFE-OCC: A novelty detection framework for Convolutional Neural Network sensors and its application in process control. (September 2022) - Pulsipher, Joshua L.; Coutinho, Luke D.J.; Soderstrom, Tyler A.; Zavala, Victor M.
Abstract: We present a novelty detection framework for Convolutional Neural Network (CNN) sensors that we call Sensor-Activated Feature Extraction One-Class Classification (SAFE-OCC). We show that this framework enables the safe use of computer vision sensors in process control architectures. Emergent control applications use CNN models to map visual data to a state signal that can be interpreted by the controller. Incorporating such sensors introduces a significant system operation vulnerability because CNN sensors can exhibit high prediction errors when exposed to novel (abnormal) visual data. Unfortunately, identifying such novelties in real-time is nontrivial. To address this issue, the SAFE-OCC framework leverages the convolutional blocks of the CNN to create an effective feature space to conduct novelty detection using a desired one-class classification technique. This approach engenders a feature space that directly corresponds to that used by the CNN sensor and avoids the need to derive an independent latent space. We demonstrate the effectiveness of SAFE-OCC via simulated control environments. Highlights: Present novelty detection framework for convolutional neural net (CNN) sensors. CNN sensors enable incorporation of image data into control architectures. Novelty framework enables robust predictions by CNN sensors.